2002
DOI: 10.1093/annonc/mdf290
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of cisplatin and vinorelbine in patients with metastatic breast cancer

Abstract: Cisplatin plus vinorelbine is active and tolerable in metastatic breast cancer, in untreated and pretreated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Our series was commenced following evidence of good tolerance to MVP in lung cancer patients (Ellis et al, 1995), and shows very similar results to those reported above (Vassilomanolakis et al, 2000;Mustacchi et al, 2002). An ORR of 32% in a population of frequently heavily pretreated patients (92% of patients previously treated with anthracyclines and 28% with taxanes) is an encouraging result.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Our series was commenced following evidence of good tolerance to MVP in lung cancer patients (Ellis et al, 1995), and shows very similar results to those reported above (Vassilomanolakis et al, 2000;Mustacchi et al, 2002). An ORR of 32% in a population of frequently heavily pretreated patients (92% of patients previously treated with anthracyclines and 28% with taxanes) is an encouraging result.…”
Section: Discussionsupporting
confidence: 79%
“…Carboplatin has been tested in the same first-line setting and shown better tolerability in some studies, although less convincing results in terms of response rate (Kolaric and Vukas, 1991;Brambilla et al, 1993). Two recent reports showed that cisplatin in combination with vinka-alkaloids may be a very well-tolerated regimen as an alternative to taxanes after anthracyclines failure (Vassilomanolakis et al, 2000;Mustacchi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cisplatin is a first-line therapy for metastatic breast cancer. Cisplatin and gemcitabine have single-agent activity in metastatic breast cancer, and preclinical data support synergy of the combination [14]. Cisplatin is one of the major chemotherapeutic weapons used against different human cancers, although its mechanism of apoptosis induction is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of phase II trials have been performed which have generally shown encouraging activity with an acceptable safety profile ( [80][81][82][83] and Capecitabine, 84-88 which will be separately discussed. Several triplets have also been investigated but increased toxicity should be expected.…”
Section: Combination Regimens With Vinorelbinementioning
confidence: 99%